P‐gp activity and inhibition in the different regions of human intestine ex vivo. (14th November 2016) - Li, Ming; de Graaf, Inge A.M.; de Jager, Marina H.; Groothuis, Geny M.M.
Abstract: Although intestinal P‐glycoprotein (P‐gp) has been extensively studied in vitro and in animals, its activity and the consequences of P‐gp inhibition for drug disposition and toxicity in humans are still difficult to accurately extrapolate from these studies. Moreover, existing in vitro models do not take into consideration that the intestine is heterogeneous with respect to P‐gp expression. Recently, we reported rat precision‐cut intestinal slices (PCIS) as a physiological ex vivo model to study the regional gradient of P‐gp activity and inhibition. Here we extended the application of PCIS to the human intestine. For this purpose rhodamine 123 (R123) accumulation in the presence or absence of the P‐gp inhibitors verapamil, cyclosporine A, quinidine, ketoconazole, PSC833 and CP100356 was measured in PCIS of human duodenum, jejunum, ileum and colon. R123 accumulation in the presence of the P‐gp inhibitors appeared to be most enhanced in the ileum compared to the other regions. Moreover, the regional differences in accumulation are in line with published differences in abundance of P‐gp. The rank order of the potency of the P‐gp inhibitors, reflected by their IC50, was comparable to that in rat PCIS. However, the increase in accumulation of the P‐gp substrate R123 by the inhibitors was larger in human ileum PCIS than in rat PCIS, indicating species difference in P‐gp abundance. These data show that human PCIS are an appropriate ex vivo model to study the activity of intestinal P‐gp and predict the inhibitory effect of drugs and of transporter‐mediated drug‐drug interactions in the human intestine. Copyright © 2016 John Wiley & Sons, Ltd.